Effect of added mixture of red beet (Beta vulgris) and (Malva parviflora) leaves as antioxidant in fingerlings diet and its effect on some growth parameters of (Cyprinus carpio L.) - Musa Saleh, Jafar; Awahd, Haifa Ali; Saleem, Hamzah Chichan (Journal of Kerbala for Agricultural Sciences, 2018)
An experiment was carried out at agriculture college university of karbala to study the effect of red beet (Beta vulgris) meal and mallow(Malva parviflora) mixture meal with different concentrations as antioxidant on growth parameters and the nutritional value of fingerlings diet (Cyprinus carpio L.) the mixture (1.5,10%) to (A,B,C) and D as control treatment with initial weight 11.68g/fish in duplicates with five fish in each treatment. Results showed that there were significant difference in diet composition between treatments during storage there was no influence on protein content in (TC) .They were 28.88% and 28.84% at the begging and the end of storage respectively. (TC) gave the best result at (p<0.01) in total weight gain weight increasing daily, the relative growth rate, feed conversion rate, feed efficiency ratio and the survival rate. (TC) was the best in deacreasing oxidation at TBA value it was 1.98 mg malonaldehyde/kg at the end of storage according to ( TA and TB) were 3.83 ,2.27 mg malonaldehyde/kg respectively and treatment (D) control appeared high value in TBA was 6.13 mg malonaldehyde/kg.